Kelayakan Bisnis Finansial Produksi Implan Biomedis Dengan Menggunakan Proses Manufaktur Aditif - Suganta Handaru Setiawan; Raden Aswin Rahadi; Erman Sumirat (Journal of Economic, Bussines and Accounting (COSTING), 2023)
The market size of medical implant in Indonesia is estimated around US$ 20 million in 2021 and will reach a value US$ 36,67 million by 2026 with 15.2% CAGR. Furthermore, the total medical implant market size in Asia was estimated US$ 7.302 million and is expected to growth become US$ 10,610 million in 2026. Those number bring medical implant business become very attractive market potential to be developed and produced in Indonesia, to meet local demand as well as for Asia market. The feasibility study is carried out using capital budgeting method by analyzing result of net present value (NPV), internal rate of Return (IRR), payback period (PP) and profitability index (PI). In addition, sensitivity analysis is performed to assess the susceptibility of the NPV result toward change in the variables input. Based on the analysis, the investment project is feasible and accepted where the NPV is USD 6.252.653, IRR 35%, and payback period 3,7 years. Sensitivity analysis also reveals that this project exhibits a relatively low susceptibility to variable uncertainty where NPV is still positive when subjected to various variables changes. Sales volume and selling price are variables that greatly influence into the change of NPV result into ±37% variance where 20% increase of sales volume in each period will dramatically increase the NPV into USD 8.584.201. Meanwhile 20% reduction of sales volume will reduce the NPV into USD 3.919.321.